ضرورة عصرنة القطاع الفلاحي كمصدر للتنمية الاقتصادية (في القانون الجزائري) - يوسفي ., مباركة; لكحل, عائشة (unuversity of eloued- جامعة الوادي, 2022)
من أجل النهوض بالنمو الاقتصادي بواسطة القطاع الفلاحي واتخاذه كمصدر لمداخيل الاقتصاد الوطني وتحقيق القدر الكافي من الاكتفاء الذاتي لابد من خلق فعالية إنتاجية في الزراعة عن طريق توفير متطلبات تنمية هذا القطاع فيجب على الدولة الجزائرية الاهتمام بالقطاع الفلاحي نظرا لما يوفره هذا القطاع من متطلبات الشعب وقدر معين من الأمن الغذائي بالإضافة إلى القضاء على جزء كبير من البطالة والفقر وكذلك تنويع مداخيل الاقتصاد الجزائري خارج قطاع المحروقات، وهذا كله من أجل تفادي الأزمات الاقتصادية نتيجة تراجع أسعار النفط في السوق الدولية مثلا.Given the difficult conditions that the Algerian economy has experienced as a result of the collapse in oil prices in the international market, which led to a significant decline in incomes as a result of this drop in prices, the Algerian state has nothing but to pay attention to other sectors, including the agricultural sector, and invest in it by preparing programs It has its own development plan aimed at sustainable development, so encouraging investment in the agricultural sector is the first alternative policy besides the hydrocarbon sector.
The necessity of developing and modernizing the agricultural sector as a source of economic development in the Algerian law
مقال
Keywords: الاستثمار ; الفلاحة ; التنمية الاقتصادية ; المحر ; قات; Agricultural investment, low oil prices, economic development.